Critical conversations in teacher education : contemporary Australian perspectives - Stokes, Helen; Davies, Larissa McLean (Emerald Publishing Limited, 2025)
This is a time of challenge for teachers with burgeoning workloads and unsustainable conditions, parental demands and challenging student behaviour. Within this climate of challenge, including that of teacher retention, education systems around the world have had to develop strategies to professionalise and improve the status of teaching. Divided into three distinct sections covering the future of teacher professionalism, reimagining pedagogical practices in challenging contexts, and professional learning to meet the needs of the profession, Critical Conversations in Teacher Education explores issues across the lifespan of teaching, including initial teacher education and in service professional learning. Drawing on research conducted broadly in the Australian educational space, chapter authors discuss the areas of culturally responsive practice, AI, climate change, classroom environments, micro credentials, and teacher retention. The research covers a wide range of settings, from early childhood through to primary and secondary settings as well as exploring a wide range of topics that are of interest to educators both in schools and at a system level and offers valuable considerations for shaping the future of the teaching profession.
Keywords: Teachers -- Training of -- Australia.; Critical pedagogy.; Education -- Teacher Training & Certification.; Teacher training.; elektronické knihy; electronic books